13‐Oxo‐9(Z), 11(E), 15(Z)‐octadecatrienoic Acid Activates Peroxisome Proliferator‐Activated Receptor γ in Adipocytes. Issue 1 (27th November 2014) - Takahashi, Haruya; Hara, Hideyuki; Goto, Tsuyoshi; Kamakari, Kosuke; Wataru, Nomura; Mohri, Shinsuke; Takahashi, Nobuyuki; Suzuki, Hideyuki; Shibata, Daisuke; Kawada, Teruo
Abstract: Peroxisome proliferator‐activated receptor (PPAR)γ is expressed in adipose tissue and plays a key role in the regulation of adipogenesis. PPARγ activators are known to have potent antihyperglycemic activity and are used to treat insulin resistance associated with diabetes. Therefore, many natural and synthetic agonists of PPARγ are used in the treatment of glucose disorders. In the present study, we found that 13‐oxo‐9( Z ), 11( E ), 15( Z )‐octadecatrienoic acid (13‐oxo‐OTA), a linolenic acid derivative, is present in the extract of tomato ( Solanum lycopersicum ), Mandarin orange ( Citrus reticulata ), and bitter gourd ( Momordica charantia ). We also found that 13‐oxo‐OTA activated PPARγ and induced the mRNA expression of PPARγ target genes in adipocytes, thereby promoting differentiation. Furthermore, 13‐oxo‐OTA induced secretion of adiponectin and stimulated glucose uptake in adipocytes. To our knowledge, this is the first study to report that 13‐oxo‐OTA induces adipogenesis through PPARγ activation and to present 13‐oxo‐OTA as a valuable food‐derived compound that may be applied in the management of glucose metabolism disorders.